The Preaching of Prophet Musa in Improving the Integrity of the Nation's Children in the Era of Society 5.0 - Wagiman Manik; Ahmad Zaky; Muhajirah Binti Jamaluddin; Arum Wirahayuningsih; Rini Mardyani Florida (AL-ISHLAH: Jurnal Pendidikan, 2023)
This research aims to find out how to improve the integrity of the nation's children in the era of society 5.0 through effective character education. The importance of this research is because today's youth education problems are very complex, so a specific way is needed to change the character of adolescents as students in accordance with the noble goals of education, so that youth are equipped with strong character to face their future, by extracting the story of the Prophet Musa in the Qur’an so that it becomes a concept of youth education with character. The story of the Prophet Musa is one of the stories most told in the Qur’an with its competencies such as politics, education, culture, youth, and the story of dealing with the rebellious of Israel, so the story of the Prophet Musa should be one of the ways of educating youth with character.  This study uses descriptive qualitative methods with library research. Research shows that the Qur'an contains character education methods, such as the story of Prophet Musa a.s. The method of proselytizing the Prophet Musa was very effectively and efficiently applied by educators in strengthening character education as an effort to increase the integrity of the nation's children to achieve community goals in the 5.0 era. research will become a basic concept in making models, methods and learning strategies for youth in the 5.0 era.